The Effect of Top management commitment on Operational Performance: The Mediating Role of Green Production - Abdulameer, Safaa Abid Ali; Mohammed, Ihab Zeyad (South Asian Journal of Social Sciences and Humanities, 2024)
The research examined the effect of top management commitment (TMC) on operational  performance and the mediating effect of green production. The study selected 219 manufacturing  companies of Iraq. The result analyzed the direct effect of TMC on green production and  operational performance. Also, the effect of green production on operational performance is  analyzed. In addition, the mediating effect of green production between the association of TMC and operational performance analyzed. So, the direct and also indirect results found in the study  were significant. This finding offers crucial understanding for managers in the manufacturing  business, indicating that a strong commitment from top management and the use of green  production may improve operational performance. Moreover, this study expands on the findings  of prior research about the correlation between TMC and GP in enhancing OP. Therefore, this  study enhances the existing research in Structural Equation Model (SCM).
Keywords: top management commitment; manufacturing industry; green production; operational performance